PERAN SASTRA DALAM PENGEMBANGAN LITERASIBERBAHASA ANAK PADA SISWA KELAS II DI SDN LONTAR BARU - Ani Ani; Fanina Gustiawati; Desty Endrawati Subroto (CV. Denasya Smart Publisher, 2024)
The role of literature is very important for students because of the positive impact it has on their academic and personal development, including the improvement of their critical thinking skills. Students will learn to analyze storylines, characters, and themes, as well as evaluate different perspectives and meanings in a text. Literary education can also enrich vocabulary and language skills. Reading a variety of literary genres expands students' vocabulary and improves their ability to understand and use language effectively. The purpose of this study is to determine the role of literature and the development of language skills of grade II students of Lontar Baru State Elementary School in the 2024/2025 school year. In this study, literature review methodology was used, and narrative literature review was chosen as the model. This narrative report analyses and summarizes data from various journals. This research employed a qualitative methodology using secondary data from relevant journals. The researcher used descriptive analysis techniques to collect, identify, organize and analyze the various data found. The results of the study highlighted the role of intensive reading programs in school literacy programs, the use of technology in literary education, interactive learning methods and children's language skills training in the form of special training. This indicates teacher development.